Comparing the predictive performance of different lymph node staging systems for postoperative overall survival in patients with ampullary carcinoma - Li, Xun; Chen, Lin; Li, Junli (Frontiers in Surgery, 2023)
Aim This study was to analyze and compare the predictive performance of the 7th and the 8th edition American Joint Committee on Cancer (AJCC) N staging system, lymph nodes ratio (LNR) and log odds of positive lymph node (LODDS) for the survival of patients with ampullary carcinomas (ACs). Method This retrospective cohort study included patients with primary ACs after surgery from the Surveillance, Epidemiology, and End Results (SEER) 2004–2015. Univariate and multivariate Cox proportional hazard models were used. The study population was divided into a training set and a testing set in a ratio of 7–3. The C-index and area under the curve (AUC) were used to compare the predictive performance of the four staging on overall survival (OS) in the training set and the testing set. Results A total of 7,480 patients with primary ACs (1,178 survived and 1,128 dead) were in this study. The average follow-up time was 41.1 months. N1 stage and N2 stage of the 8th edition AJCC N staging system, LNR staging (0–0.3), LNR (>0.3), LODDS (−2.4 to −0.8) and LODDS (>−0.8) were associated with OS in AC patients after adjusting for age, race, pT stage, tumor size, grade, radiation, and insurance. The C-index of the 7th AJCC N staging was significantly lower than the C-index of the 8th AJCC N staging in the training set [0.608 vs. 0.629, P < 0.001] and testing set [0.635 vs. 0.658, P < 0.001]. The C-index of the LODDS staging was significantly higher than the C-index of the 8th AJCC N staging in the training set [0.641 vs. 0.629, P = 0.034] and testing set [0.671 vs. 0.658, P = 0.034]. LODDS staging may be a potential predictor of OS at 6 months [AUC = 0.687], 12 months (AUC = 0.692), and 48 months (AUC = 0.709), and LNR staging (AUC = 0.655) may be a potential predictor of OS at 24 months in AC patients. The predictive ability of LNR staging and LODDS staging were also found in different subgroups. Conclusion The LNR and LODDS staging systems' predictive performance for OS of AC patients were superior to the 8th edition AJCC N staging system, especially in patients ages ≥65 or with higher tumor grade (grade II and III). The LNR staging and the LODDS staging were potential predictors for 24-month OS, and 6, 12, 24 and 48-month OS, respectively.